ANALISIS MEKANISME PERHITUNGAN BAGI HASIL AKAD MUDHARABAH PADA PRODUK TABUNGAN TAAT iB DI BPRS DAYA ARTHA MENTARI KANTOR CABANG GEMPOL KABUPATEN PASURUAN - Rovi Nurhidayati; Muhammad Fahmul Iltiham; Alimatul Farida (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2022)
The banking industry is currently competing to provide convenience in meeting the needs of a growing community. One of them is the community's need for lifestyle changes that are increasingly modern, which is one of the banking opportunities to help, namely through fundraising called Savings. BPRS Daya Artha Mentari KC Gempol as a pioneer of Islamic banking in Indonesia has also created products to help its customers obtain fundraising services with various types of programs, one of which is the iB TaaT Savings. In this study, using a descriptive method. The data collection method that the author uses is literature study, observation, recording, and interviews. Based on the research conducted by the author, the author can conclude that this study is entitled Analysis of the Mechanism of Calculation of Profit Sharing for Mudharabah Contracts on TaaT iB Savings Products at BPRS Daya Artha Mentari KC Gempol according to an Islamic Economics review. TaaT iB Savings is a savings product with the mudharabah principle. Therefore, the authors are interested in further researching how exactly the iB TaaT Savings is, and how the function of the Education Savings is for both the bank and the customer and how the Islamic economy reviews the iB TaaT Savings.